PENGARUH INVESTMENT OPPORTUNITY SET (IOS) DAN MEKANISME CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN LQ45 TAHUN 2015-2017 - Jerry Juarsa; Abu Kosim; Eka Meirawati (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2019)
This study aimed to examine how the effect of the Investment Opportunity Set (IOS) and the Mechanism of Corporate Governance on LQ45 Company Values for 2015-2017. This type of research is quantitative. The sample selection were conducted by the purpose sampling method. The number of samples used was 13 companies with observations for 3 years. Data were analyzed with using the multiple linear regression. The results of the study showed that the Investment Opportunity Set (IOS) had an effect on company value and corporate governance mechanisms proxied by the audit committee, independent board of commissioners, institutional ownership and managerial ownership did not affect LQ45 company value.